Physical Properties and Digestibility of Resistant Starch from Phosphorylated Sago Starches - Polnaya, Febby J.; Marseno, Djagal W.; Cahyanto, Muhammad N. (Pakistan Journal of Nutrition, 2018)
Background and Objective: Native sago starch (NSS) was phosphorylated white sodium tripolyphosphate (STPP) or phosphorous oxychloride (POCl3) to increase the properties of starch. The phosphorylated sago starch play a significant role in forming new structure that affect the physical properties and in vitro digestibility of resistant starch (RS). The objective of this study was to investigate the effects of the reaction of NSS with STPP or POCl3 at pH 8, 9, 10 and 11 on the physical properties and in vitro digestibility of RS. Materials and Methods: The RS from NSS was prepared by phosphorylating with 5% STPP or 4% POCl3 at pH 8-11 for 1 h. The functional groups, relative degree of cross-linking, degree of crystallinity of selected RS samples and RS contents, were also investigated. Results: The FT-IR spectra showed that after being hydrolyzed, RS contains α,γ-dextrin enriched with phosphate groups. The di-starch phosphate had relative degrees of cross-linking ranging from 22.83-85.33%, while that mono-starch phosphate had not able to estimate. The XRD pattern indicated that the crystalline structure of RS was destroyed. The mono- and di-starch phosphate had degrees of crystallinity ranging from 6.53-6.64%. Compared with NSS, the RS contents of mono- and di-starch phosphate were higher by 20 and 40%, respectively. The RS content of phosphorylated starch was affected by the substitution of phosphate groups. Conclusion: The RS from mono- and di-starch phosphate were affected by the presence of the phosphorus group in the structure and the RS content could be improved greatly with phosphorylation. The RS content of di-starch phosphate was increased with increasing pH of the reaction mixture. X-ray patterns of RS from native and phosphorylated sago starches indicated that a crystalline structure transformation of those starches took place during preparation of RS.